The Role of Fathers in the Emotional Development of Early Childhood - Farah Maulida Salsabilla; Mutiara Syahrani Porang (Socrates: Journal of Education, Philosophy and Psychology, 2025)
Because the child struggles to manage emotions, they exhibit aggressive behavior in their teenage years. This type of behavior has been shown since early childhood because of insufficient interaction with parents. As a result, in today’s world, the father figure’s influence on children’s emotional growth is still viewed as overlooked. This article aims to explore the significance of the fathers in the emotional growth of young children. This study consists of literature review. A literature review involved seeking out and analyzing literature by studying different journals, books, and other published materials relevant to the research subject to create a written piece about a particular topic or issue. The importance of the father figure in emotional development offers notable advantages for boys in personal growth, impulsive regulations, and social adaptation during adolescence. At the same time, girls assigned the role of a father typically do not engage in sexual promiscuity during their youth and can establish healthy relationships with men later in life. A father’s role in parenting involves overseeing the child’s emotions, which affects their social-emotional growth. The lack of a father can adversely affect a child’s growth. Consequently, the engaged participation of fathers and solid emotional support are crucial in fostering a positive character and ensuring children’s future well-being.